Natural Approaches to Crop Protection and Soil Conservation - Laville, Nelson (Inter-American Institute for Cooperation on Agriculture (IICA), 2023)
Guest speakers: Mr. Nelson Laville, Plant Pathologist, Phyto-Sol Plus Inc. - Dominica, Mr. Damian Adjodha, Agroecological production specialist, New Flower Regenerative Garden - St. Lucia